Laparoscopic Evaluation and the Management of the Nonpalpable Testis. Issue 2 (1997) - Koyama, Toshiki; Nonomura, Katsuya; Ameda, Kaname; Kakizaki, Hidehiro; Matsugase, Yasukuni; Shinno, Yuichiro; Kanno, Takayuki; Yamashita, Tetsufumi; Murakumo, Masashi; Koyanagi, Tomohiko
Abstract : From June 1992 to December 1996, we performed laparoscopic evaluation for 28 nonpalpable testes in 22 patients (1–21, median 3 years old). The location of 28 testes were divided into 4 categories according to the classification by Malone et al .: canalicular in 17 testes, just canalicular in 2, abdominal in 7, and absent in 2. Two-stage Fowler–Stephens orchiopexy was performed in 3 abdominal testes and planned two-stage orchiopexy was performed in one abdominal testis, while one-stage standard orchiopexy was performed in 10 testes (canalicular 5, just canalicular 2, and abdominal 3). In 10 of 17 canalicular testes no testicular element was found on histological examination of the excised remnant tissue. In two completely absent testicular structures, as verified by vanishing spermatic vessels, no further exploration was done after laparoscopy. There was one complication in this series: jejunal injury which needed oversewing, otherwise there was no postoperative sequela in all cases. Laparoscopic evaluation in patients with nonpalpable testes gives us precise information as to the existence and location of the testicle which is helpful in determining subsequent appropriate procedure and avoiding unnecessary abdominal exploration.